Effects of salicylic acid, Fe(II) and plant growth-promoting bacteria on Cd accumulation and toxicity alleviation of Cd tolerant and sensitive tomato genotypes. (15th May 2018) - Wei, Ting; Lv, Xin; Jia, HongLei; Hua, Li; Xu, HuiHui; Zhou, Ran; Zhao, Jin; Ren, XinHao; Guo, JunKang
Abstract: In this study, we investigated the ameliorative effects of salicylic acid (SA), metal ion (Fe( II)), and plant growth-promoting bacteria Burkholderia sp. D54 (B) on two tomato genotypes with different Cd tolerances under Cd stress, viz. Liger (Cd tolerant) and Tabd (Cd sensitive). The plant biomass, Cd accumulation, antioxidative response, pigment content and photosynthetic performance were determined. According to the results, exogenous application of SA, Fe( II) and Burkholderia sp. D54 or their complex effectively reduced Cd accumulation and increased biomass of root, stem and leaves in both Cd sensitive and Cd tolerant genotypes. Among all treatments, SA+Fe+B exerted the best performance. Burkholderia sp. D54 effectively alleviated Cd-induced oxidative toxicity in both tomato genotypes, while SA ameliorated oxidative stress in Cd sensitive genotype. Photosynthetic pigment content and photosynthetic rate of Cd tolerant genotype was increased by all treatments, but only SA and Burkholderia sp. D54 treatment increased pigment contents and photosynthetic performance in Cd sensitive genotypes. All treatments significantly decreased Cd accumulation in both tomato genotypes. The effect of Cd reduction was Fe+SA+B>SA>Fe>B. Taken together, our results indicated that exogenous application of SA, Fe( II) and Burkholderia sp. D54 could alleviate the Cd toxicity in both Cd sensitive and Cd tolerant genotypes, although the extent varies. Graphical abstract: Image 1 Highlights: SA, Fe(II), Burkholderia sp. D54 application reduced Cd accumulation and increased biomass of tomato plants. SA, Fe(II), Burkholderia sp. D54 complex was most effective in reducing Cd content and increasing plant biomass. Burkholderia sp. D54 alleviated oxidative toxicity of both Cd-sensitive and Cd-tolerant tomato genotypes. SA alleviated oxidative toxicity of Cd-sensitive tomato genotype. SA and Burkholderia sp. D54 increased the photosynthetic pigment content and photosynthetic rate of both tomato genotypes.